Hans J. Massaquoi’s Destined to Witness as an Autobiographical Act of Identity Formation - Alexandra E. Lindhout (Current Objectives of Postgraduate American Studies)
In his autobiography, Hans J. Massaquoi describes the discrimination he encountered in Nazi Germany and Liberia because of his mixed racial background. Throughout his life Massaquoi had to cope with identity crises. Through the self-therapeutic discourse in the form of his autobiography, however, Massaquoi developed his hybrid transatlantic African American and African German identity.